2013
DOI: 10.1371/annotation/3f97e271-6926-4766-8430-1b4a009e80c6
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Novel Genes Associated with Colorectal Cancer Are Revealed by High Resolution Cytogenetic Analysis in a Patient Specific Manner

Abstract: Genomic abnormalities leading to colorectal cancer (CRC) include somatic events causing copy number aberrations (CNAs) as well as copy neutral manifestations such as loss of heterozygosity (LOH) and uniparental disomy (UPD). We studied the causal effect of these events by analyzing high resolution cytogenetic microarray data of 15 tumor-normal paired samples. We detected 144 genes affected by CNAs. A subset of 91 genes are known to be CRC related yet high GISTIC scores indicate 24 genes on chromosomes 7, 8, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The MREII exonuclease creates DNA nicks guiding the SPO11-TOPOVIBL complex to accurately catalyze DSBs along the genome in specific hotspots [133,134]. Aberrant expression of SPO11 has been found in cell lines of melanoma and also lung cancer [135], see Figure 3, acute myeloid leukemia (AML) [136], cutaneous T-cell lymphoma (CTCL) [137] as well as in patient samples of melanoma, [135,138], cervical cancer [135], gastric cancer [138], and CTCL [139]. Although the exact mechanism of SPO11 reactivation in cancer cells remains elusive, it has been shown that in CTCL, it is regulated epigenetically and temporary expressed at the onset of the cell division in G1/S phase transition [139].…”
Section: Melanoma and Meiosis Specific Ct (Meict) Genesmentioning
confidence: 99%
“…The MREII exonuclease creates DNA nicks guiding the SPO11-TOPOVIBL complex to accurately catalyze DSBs along the genome in specific hotspots [133,134]. Aberrant expression of SPO11 has been found in cell lines of melanoma and also lung cancer [135], see Figure 3, acute myeloid leukemia (AML) [136], cutaneous T-cell lymphoma (CTCL) [137] as well as in patient samples of melanoma, [135,138], cervical cancer [135], gastric cancer [138], and CTCL [139]. Although the exact mechanism of SPO11 reactivation in cancer cells remains elusive, it has been shown that in CTCL, it is regulated epigenetically and temporary expressed at the onset of the cell division in G1/S phase transition [139].…”
Section: Melanoma and Meiosis Specific Ct (Meict) Genesmentioning
confidence: 99%
“…From our previous exon profiling study [ 27 ], we selected MUC4 and ADAM12 for further analysis, as they had the highest, most significant exon-level expression changes. In patients with CRC, alterations of these two genes were reported at multiple levels, including the cytogenetic, gene expression and splicing levels [ 27 , 28 ]. In the present work, we assessed the prognostic significance of these two genes in CRC using The Cancer Genome Atlas (TCGA) database, which was preceded by confirming their differential expression in our patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a significant reduction in both GFAT-1 and DPM1 expressions in metastatic melanoma cells treated with anandamide, which may suggest that the biosynthesis of glycans in these cells was downregulated. As shown in the literature, GFAT-1 and DPM1 overexpression is of a cell/patient specific manner [62], but the activity of the enzymes encoded by the investigated genes may also be influenced by several genetic and metabolic alterations [63]. During the epithelial-to-mesenchymal transition (EMT) of A549 lung cancer cells, the glucose uptake was intensified, but instead of increasing the glycolysis, the glucose was directed to the HBP pathway [64].…”
Section: Discussionmentioning
confidence: 96%
“…Altered DPMs gene expression level and enzyme activity (the only known mannose donor for mannosylation in the lumen of the endoplasmic reticulum) in humans is linked to cancer and congenital disorders of glycosylation [67,68]. The DPM1 gene plays a crucial role in colorectal cancer [62] and breast cancer, but its expression measured by means of the microarray analysis in tissue samples obtained from patients with breast cancer showed significant differences in values ranging from 761 up to even 5424 [69]. Considering this information, the obtained result confirmed the cell-dependent differences in the overexpression of the investigated genes.…”
Section: Discussionmentioning
confidence: 99%